Analisa ekonomi usaha peternakan broiler yang menggunakan dua tipe kandang berbeda - Imam Ismail; Hari Dwi Utami; Budi Hartono (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2013)
This study aims at analyzing economic calculations of broiler farm activities which applied two different housing systems (closed and opened house system) at Malang Regency. Data were collected from two selected broiler farmers from April 15th to May 11st, 2013. Then the data were analyzed using economic and descriptive method. The results show that farmers who applied closed housing system were able to earn more profit (Rp2.214,-/bird/period) than those who applied opened housing system (Rp1.875,-/bird/period). However, farmers with closed housing system paid higher pro-duction costs than those with the opened housing system. Another findings show that both (closed and opened house) systems were economically viable for broiler production since they provide a good R/C ratio. This study suggests broiler farmers who tend to apply closed housing systems should modify the equipments which require higher costs.Keywords: Broiler farming, R/C ratio and BEP